Dynamic Characterization of Macrobending Loss Optical Fiber-Based Load Sensor - Widiyatmoko, Bambang; Rofianingrum, Mefina Y. (Talenta Publisher, 2021)
The weight of vehicles passing through the road greatly affects road damage, so it is necessary to have a non-stop weighing system or Weight in Motion (WIM). In this study, the dynamic characterization of the WIM sensor was carried out based on the principle of optical fiber macrobending. In this study, a single-mode step-index optical fiber was used as the sensor material and a laser diode with a power of 5 mW and a wavelength of 1,550 nm as a light source. Characterization was carried out by running over the sensor using a motor with three variations of speed, namely 10 km/hour, 15 km/hour, and 20 km/hour. Two different conditions were also carried out, namely, the sensor was directly crushed and the sensor was reinforced in the form of a half-cylinder wooden beam. The test was carried out with three different types of sensors. From the observations, data shows that the addition of a beam can increase the accuracy of the reading as seen from the smaller the difference in the output voltage reading for the same type of sensor and vehicle speed. Besides that, there is a strengthening of the sensor resistance up to 10 times which is known from the sensor output voltage where the voltage at the addition of the beam is 1/10 of the reading without the beam. This is due to an increase in the sensor area exposed to the load.